Self-Regulation with Burnout of Basarnas Employees - Itryah; Haries Kurnianto (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study aims to find out and explain empirically the relationship between self-regulation and burnout in Basarnas employees in Southern Sumatera. The independent variable in this study is self-regulation, and the dependent variable in this study is burnout. The population in this study were Basarnas employees spread across the southern part of Sumatera, totaling 447 people. Based on the Isaac and Michael formula with an error rate of 5%, a population of 139 people is obtained. This research uses quantitative methods. The sampling technique used in this study is simple random sampling. The measuring tools used in this study are the self-regulatory behavior scale and the burnout scale. The self-regulation scale is 60 items with a reliability of 0.585 and the burnout scale is 60 items with a reliability of 0.765. Data validity used the person's product moment (r) correlation technique with the output system of a reliability package, and data reliability used the Cronbach alpha technique with the help of the IBM SPSS program version 21.00. Based on the results of data analysis using the IBM SPSS program version 21.00, the results obtained were a coefficient of R = 0.600 with a value of (R2) = 0.361 and p = 0.000 where p < 0.01. So, the result is a very significant relationship between self-regulation and burnout in Basarnas employees in southern Sumatra. Based on the results of the analysis, the value of the contribution given by self-regulation and burnout is R² = 0.361 or 36.1% so there is still another 63.9% which is influenced by other factors not involved in this study.